Stuff of nightmares : no holiday for murder - Stine, R. L. (Boom! Studios, 2024)
Get into the sinister spirit of the season and join The Nightmare Keeper for two fresh forays into the Stuff of Nightmares universe! First, comic creator Alex Oxaca has been out of the spotlight for decades, and he'll wish he'd remained in obscurity soon enough... RED MURDER was the smash hit title of the early 2000s, and will come back from the past in more ways than one during the 20th anniversary celebration of the title! A real ax murderer, eerily parallel to the hatchet-wielding killer in the comic, starts chopping down equally real victims, bringing a whole new meaning to HorrorCon. And...as malls continue to die, a down-and-out former mall Santa named Heinrick Fiddler's rage turns to madness, and he's dead-set on making sure department store shopping isn't the only thing that's deceased in SLAY RIDE! Bestselling Fear Street and Goosebumps author R.L. Stine is joined by Bram Stoker Award-nominated artist Pius Bak (Eat the Rich) and acclaimed artist Adam Gorham (Dune: Blood of the Sardaukar, The Blue Flame) for two standalone tales directly from your most demented dreams!